PERKEMBANGAN HUBUNGAN BILATERAL INDONESIA – BULGARIA MELALUI DIPLOMASI BUDAYA (STUDI KASUS : WORLD CHAMPIONSHIP OF FOLKLORE 2014) - Mhd. Dirga Prasmana; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research describes the development of relationship between Indonesia and Bulgaria through cultural diplomacy. Its main objectives are to provide greater knowledge and deep understanding of Indonesian national interest through cultural diplomacy to improve bilateral relations with the Government of Bulgaria. In order to improve this relationship, Indonesia uses World Championship of Folklore 2014 as a tool of diplomacy.The method that is used in this research is qualitative research. Some of the datas are obtained from books, journals, articles, internet and other media. This research focuses on the improvement of Indonesia-Bulgaria relationship by using World Championship of Folklore 2014 as a diplomacy tool. This research uses the Cultural Diplomacy theory and Multi-Track Diplomacy theory.Using World Championship of Folklore 2014 as a tool is an effective way of diplomacy by Indonesian government. World Championship of Folklore 2014 is a stepping stone to attract the attention of the world and Bulgaria in particular. Multi-track diplomacy that was done by Indonesia was successful. It is proved by many cooperation and improvement between Indonesia and Bulgaria and not only in cultural field and not only on cultural field but also cooperation on other fields.Keywords: Indonesia, Bulgaria, World Championship of Folklore, cultural diplomacy.